Strengthening SMEs through Rapid Prototyping to Meet Future Challenges - Why & How? - Ahmad, Ayyaz; Mazhar, Muhammad Ilyas; Van Voorthuysen, E. (Institute for Manufacturing, University of Cambridge, 2009)
In the current scenario of the global economic crisis, market uncertainty, layoffs, shrinkage in market size are some common issues which the business is facing and at the same time looking for some way outs. This situation demands the reconfiguration of existing theories, models or frameworks so that innovative solutions can be developed to ease the situation. Technology like Rapid Prototyping have the potential to meet certain future challenges, but there is a dire need to blend the technology and strategy together to end up with a viable solution, unfortunately there is no one and simple solution, but joint efforts by different stakeholders is the need of time. A recent trend is the globalization of the production operations in which the manufacturing is done basically in the developing countries largely through SMEs but the question is that are these small to medium entrepreneurs ready to take the challenge of the fast changing requirements and is it possible to meet these challenges without building the capacity of the these small companies? This paper take a closer look of the SMEs by giving an in depth analysis of the inherent problems and challenges such companies are facing and how the technology like RP can assist them to come out of this situation. The paper also highlights the role of the stakeholders including both government and non government organisations including universities and provides valuable recommendations for the capacity building of these small to medium companies, which will not only boost the local economies but will also facilitate the international production & operations management in a better and most effective way.